Who Needs Traditional Values? The Problem of Integrating Traditional Cultures into Modern Society - E. E. Marchenko; V. G. Oreshkin; O. V. Plebanek (Дискурс)
Introduction. The article analyzes the basic concepts of ethno-cultural discourse, and raises the problem of the uncertainty of the conceptual apparatus, on the basis of which the theory of intercultural interactions is built, which makes it difficult to introduce the results of research into practice. The authors propose to clarify the categories that are relevant specifically for Russia at the present time, in the context of the formation of the foundations of the state's cultural policy and the adoption of relevant legislative acts. The subject of the research is the system of categories underlying the theories of modernization and theories of cultural interactions.Methodology and sources. The analysis of the categorical apparatus of modern ethno-cultural policy is based on methodological principles that have developed in science in the process of a cultural-centric turn, which was laid down by the works of T. Parsons and P. Sorokin.Results and discussion. The paradigmatic nature and indefinite use of such categories as “traditional values” and “traditional cultures” creates conditions for speculation and does not allow building a balanced cultural policy. And the unreasonable desire to the conservation of archaic cultural patterns leads to serious contradictions in the goals and results of the implementation of cultural policy. It is concluded that in order to make effective political decisions, it is necessary to take into account the difference in the use of concepts in the social sciences and the humanities and in the political sphere. It is necessary to separate the so-called “traditional values” and archaic societies, understanding by the former the values traditional for a particular cultural system, regardless of the concept of progress. And under the second – archaic cultures (and societies, carriers of these cultures), one should understand cultures that were formed on the basis of primitive technology to ensure the viability of the population.Conclusion. In such a paradigm of cultural observation of observations of archaic cultures, one should build not only from the study of the intrinsic value of culture, but also from the disclosure of equal accessibility of humanitarian benefits (health protection, choice of occupation, accessibility of cultural achievements and education, etc.).